The equity and efficiency of electricity network tariffs - Niall Farrell; Tensay Hadush Meles (The Economic and Social Research Institute (ESRI), 2023)
We estimate the welfare implications of a cost-reflective 'Coasian' reform of electricity network tariffs using an Irish case study. We find that current Distribution Use of System (DUoS) tariffs deviate considerably from a cost-reflective structure. At the individual level, tariff reform leads to large welfare changes. However, positive welfare effects are largely cancelled out by negative welfare effects resulting in a small net welfare impacts in aggregate, up to e33 million. The distribution of incidence is strongly regressive. Households in the lowest income decile incur losses of up to e40 per annum while households in the highest income decile benefit by up to e62 per annum. Despite these effects, we show that inefficient DUoS tariffs represent a costly distributional policy. We demonstrate that it is more efficient to counter the regressive effects through the tax-benefit system.
Keywords: K32; L94; L98; Q42; Q48; Q51; Q53; Q54; Q55; 330; Electricity Tariffs; Distortion; Welfare Loss; Distributional Impacts